2022
DOI: 10.1126/scitranslmed.abg1046
|View full text |Cite
|
Sign up to set email alerts
|

Inverted direct allorecognition triggers early donor-specific antibody responses after transplantation

Abstract: The generation of antibodies against donor-specific major histocompatibility complex (MHC) antigens, a type of donor-specific antibodies (DSAs), after transplantation requires that recipient’s allospecific B cells receive help from T cells. The current dogma holds that this help is exclusively provided by the recipient’s CD4 + T cells that recognize complexes of recipient’s MHC II molecules and peptides derived from donor-specific MHC alloantigens, a process called indirect allorecognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Such responses would be expected to contribute to graft rejection. To that end, Charmetant and colleagues report intragraft microvascular lesions associated with donor T cell--mediated alloantibody production (1). Similarly, in our murine model of chronic antibodymediated rejection, allograft vasculopathy was diminished, and heart graft survival prolonged, when donor hearts were first depleted of T cells (3).…”
Section: Direct-pathway Allorecognition By Passenger Donor Cd4 + T Cellsmentioning
confidence: 88%
See 2 more Smart Citations
“…Such responses would be expected to contribute to graft rejection. To that end, Charmetant and colleagues report intragraft microvascular lesions associated with donor T cell--mediated alloantibody production (1). Similarly, in our murine model of chronic antibodymediated rejection, allograft vasculopathy was diminished, and heart graft survival prolonged, when donor hearts were first depleted of T cells (3).…”
Section: Direct-pathway Allorecognition By Passenger Donor Cd4 + T Cellsmentioning
confidence: 88%
“…Rather, concurrent signaling through the B cell receptor (BCR) is essential for antibody production. Charmetant and colleagues now demonstrate that increased B cell proliferation and upregulation of MHC II occurred if B cells were co-cultured with third -party T cells, but only if the BCR was simultaneously cross-linked (1). Similarly, we previously reported that adoptively-transferred third -party CD4 + T cells could provide help in T cell--deficient mice for antibody responses against a model antigen, but only if simultaneously challenged with that antigen (3).…”
Section: Direct-pathway Allorecognition By Passenger Donor Cd4 + T Cellsmentioning
confidence: 90%
See 1 more Smart Citation
“…The disorder of single-cell transcriptional heterogeneity is an inevitable outcome of persistent allosensitive responses after transplantation. Alloantigens are rapidly drained into the secondary lymphoid tissue once the graft is implanted to the recipient, activating an adaptive immune response . Afterward, donor-specific antibodies (DSAs) are produced and bound to the antigens exposed on the surface of vascular endothelial cells, activating the complement system or directly leading to endothelial cell apoptosis and detachment through cytotoxicity .…”
Section: Introductionmentioning
confidence: 99%
“…1−3 Alloantigens are rapidly drained into the secondary lymphoid tissue once the graft is implanted to the recipient, activating an adaptive immune response. 4 Afterward, donor-specific antibodies (DSAs) are produced and bound to the antigens exposed on the surface of vascular endothelial cells, activating the complement system or directly leading to endothelial cell apoptosis and detachment through cytotoxicity. 5 Endothelial cell injury not only causes the proliferation and activation of alloreactive immune cells but also promotes the infiltration of inflammatory cells, including neutrophils, monocytes, and lymphocytes, thus leading to multitype and multidimensional single-cell transcriptional disorders.…”
Section: Introductionmentioning
confidence: 99%